High Surface Area CeO2 Promoted Suzuki–Miyaura Cross-Coupling of Arylboronic Acids and Aryl Iodides - Mayer, Marilyn Graziano; Nador, Fabiana; Volpe, María Alicia; Radivoy, Gabriel (Synlett, 2013)
High surface area cerium oxide (240 m2/g) efficiently promoted the Suzuki–Miyaura cross-coupling of aryl iodides with arylboronic acids, in the absence of palladium or any other transition-metal catalyst. Excellent selectivity towards the cross-coupling product was observed. Cerium oxide could be recovered and reused at least three times without any loss of activity.
Keywords: biaryls; cross-coupling; cerium oxide; Suzuki–Miyaura reaction; palladium-free